Lung-Targeted Delivery of Dimethyl Fumarate Promotes the Reversal of Age-Dependent Established Lung Fibrosis - Kosuke Kato; Ioannis Papageorgiou; Yoon-Joo Shin; Jennifer M. Kleinhenz; Sunny Palumbo; Seongmin Hahn; Joseph D. Irish; Skye P. Rounseville; Kenneth S. Knox; Louise Hecker (MDPI AG, 2022)
Idiopathic pulmonary fibrosis (IPF), a severe and deadly form of lung fibrosis, is widely regarded as a disease of aging. We previously demonstrated that aged mice with persistent lung fibrosis and IPF lung myofibroblasts exhibit deficient Nrf2-mediated antioxidant responses. Tecfidera is an orally administered FDA-approved drug for the treatment of multiple sclerosis, where the active pharmaceutical ingredient is dimethyl fumarate (DMF), an active Nrf2 activator. However, no studies have evaluated the efficacy of DMF for age-associated persistent lung fibrosis. Here, we demonstrate that in IPF lung fibroblasts, DMF treatment inhibited both TGF-β-mediated pro-fibrotic phenotypes and led to a reversal of established pro-fibrotic phenotypes. We also evaluated the pre-clinical efficacy of lung-targeted (inhaled) vs. systemic (oral) delivery of DMF in an aging murine model of bleomycin-induced persistent lung fibrosis. DMF or vehicle was administered daily to aged mice by oral gavage or intranasal delivery from 3-6 weeks post-injury when mice exhibited non-resolving lung fibrosis. In contrast to systemic (oral) delivery, only lung-targeted (inhaled) delivery of DMF restored lung Nrf2 expression levels, reduced lung oxidative stress, and promoted the resolution of age-dependent established fibrosis. This is the first study to demonstrate the efficacy of lung-targeted DMF delivery to promote the resolution of age-dependent established lung fibrosis.